Determination of Molybdenum(VI) by Optical Sensing Film and Flow Injection Analysis - KAZEMZADEH, A. (Asian Journal of Chemistry, 2010)
Optical flow-through cell detector with incorporated transparent chemosensitive layer of Nile blue has been applied in simple, double-channel flow-injection system for food, environmental and industrial analysis. The reductant analyte converts the Nile blue based sensing layer to colourless form and the attendant colour change is used for sensing. Discoloration of the film is spectrophotometrically at 582 nm wevelength. The flow injection system has been successfully used for selective determination of molybdenum(VI). This detector was fabricated by binding Nile blue to a cellulose acetate film that had previously been subjected to an exhaustive base hydrolysis. The membrane has good durability (> 7 months) and a short response time (< 12 s). Molybdenum(VI) can be determined for the range 0.02-3.40 μg mL-1 with 3o detection limits of 7 ng mL-1. The method is easy to perform and uses acetylcellulose as a carrier. The reagents used for activating the cellulose support are inexpensive, non-toxic and widely available.